SOCIAL WORK RESPONSIBILITY TOWARDS STRESS MANAGEMENT - Reynolds, Coen (Social Work/Maatskaplike Werk, 2010)
Social work managers (the concept of manager here refers to a director of a social service organisation, head of office or supervisor, or any person who has control over two or more workers) should create and maintain a work environment (Weinbach, 2003:5) that will be conducive to maintaining the health and wellbeing of workers and contribute to the effective delivery of services. Bergh (2004:440) states that “Organisational effectiveness and employee physical and psychological wellbeing should be equally important and are interrelated”. Employees, therefore also social workers, should not leave their workplace in a worse state of health than when they arrived there (Williams & Cooper, 2002:108).